Uniportal Thoracoscopic Approach For Pulmonary Hydatid Cyst: Preliminary Results - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2018)
Purpose: Pulmonary hydatid cyst is a preventable parasitary disease with high prevalence in low-medium income countries. Thoracoscopic approach is seen in the literature as small-case groups and multiple-port incisions are observed in these studies. Unlike other thoracoscopic approaches for the surgical treatment, we describe the single-port technique for the first time in our study. We attempt to compare the clinical outcomes and preliminary results of patients with pulmonary hydatid cyst treated with either minimally invasive or thoracotomy. Methods: The medical records of 66 patients undergoing surgery for pulmonary hydatid cyst disease between January 2013 and July 2017 were reviewed. The number of patients who underwent thoracotomy was 48, whereas 18 were managed by single-port video-assisted thoracoscopic surgery. Variables statistically compared between the 2 groups were age, diameter of the cystic, operation time, volume and duration of the drainage, postoperative complications, length of stay, duration of narcotic analgesic usage, and pain score. Results: Thoracoscopic approach was superior to conventional thoracotomy in terms of operation time, drainage volume, time to drain removal, hospital stay, narcotic analgesic treatment duration, and postoperative pain scores. All thoracoscopic procedures were concluded successfully, and conversion to open surgery was not required. No postoperative mortality was seen in either group. During the follow-up period, no recurrence was encountered in either group. Conclusions: Uniportal thoracoscopic approach is a safe option for the treatment of hydatid cyst disease. It can be used as an alternative to thoracotomy, depending on the size and location of the lesion.
Keywords: capitonnage; hydatid cyst; uniportal; video-assisted thoracoscopic surgery; SURGICAL-TREATMENT; LUNG; DISEASE; CHILDREN; SURGERY; ADULTS